2006
DOI: 10.1111/j.1365-313x.2006.02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of OsAGAP, an ARF‐GAP, interferes with auxin influx, vesicle trafficking and root development

Abstract: ). † Equal contributors to this work. SummaryDevelopment and organogenesis in both dicot and monocot plants are highly dependent on polar auxin transport (PAT), which requires the proper asymmetric localization of both auxin influx and efflux carriers. In the model dicot plant Arabidopsis thaliana, the trafficking and localization of auxin efflux facilitators such as PIN-FORMED1 (PIN1) are mediated by GNOM, a guanine-nucleotide exchange factor (GEF) for the ADPribosylation factor (ARF) family of small GTPases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…4 As well, asymmetric localization of AUX1 occurs in the root cells of Arabidopsis plants, 7 and overexpression of OsAGAP interferes with localization of AUX1. 1 Our data support that ARF-GAP mediates auxin influx and auxin-dependent root growth and patterning, which involves vesicle trafficking. 1 Here we show that OsAGAP overexpression leads to enhanced gravitropic response in transgenic rice plants.…”
Section: Polar Auxin Transport (Pat) Is a Unique Process In Plantssupporting
confidence: 72%
See 1 more Smart Citation
“…4 As well, asymmetric localization of AUX1 occurs in the root cells of Arabidopsis plants, 7 and overexpression of OsAGAP interferes with localization of AUX1. 1 Our data support that ARF-GAP mediates auxin influx and auxin-dependent root growth and patterning, which involves vesicle trafficking. 1 Here we show that OsAGAP overexpression leads to enhanced gravitropic response in transgenic rice plants.…”
Section: Polar Auxin Transport (Pat) Is a Unique Process In Plantssupporting
confidence: 72%
“…3 AtPIN2 is localized at the apical side of epidermal cells and basally in cortical cells. 1,4 GNOM, an ARF GEF, modulates the localization of PIN1 and vesicle trafficking and affects root development. 5,6 The PIN auxin-efflux facilitator network controls root growth and patterning in Arabidopsis.…”
Section: Polar Auxin Transport (Pat) Is a Unique Process In Plantsmentioning
confidence: 99%
“…Among the Arabidopsis class I ARF-GAPs, only AGD3 has been demonstrated to function in plant development by affecting auxin-dependent vascular differentiation (Koizumi et al, 2005;Sieburth et al, 2006). Also, the overexpression of a rice (Oryza sativa) ARF-GAP (OsAGAP) hampered root development by interfering with the normal trafficking of auxin influx carriers (Zhuang et al, 2006). Here, we show that an additional function for class I ARF-GAPs in plants is in the maintenance of root hair growth directionality.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study revealed that GNOM controlled PAT through polar localization of PIN1 [17], a component of auxin efflux carriers. In addition, some ARF-regulating factors in rice are also related to PAT, such as the ARF-activating protein involved in the localization of AUX1, an auxin influx carrier [35]. All mutant phenotypes observed in gnom1-1 to gnom1-4, including a lack of AR, reduced number of LR, partial agravitropic response and hypersensitivity to NPA, could be explained by disrupted PAT.…”
Section: Discussionmentioning
confidence: 99%